Can Weekly Home Visits by The Community Improve Iron Supplementation Intake among Pregnant Women? - Ramadhani, Kurnia (Universitas Airlangga, 2025)
Background: Anemia is one of the significant health problems among pregnant women; one of the interventions by the government is through iron supplementation. The adherence rate among pregnant women to consume iron supplementation is still low. Objective: This study aims to determine the effectiveness of community empowerment on adherence to iron supplementation among pregnant women. Methods: This research was a mixed method with a quantitative and qualitative approach and used a quasi-experimental study. The pre-and post-tests of adherence rates were conducted using the Morisky Medication Adherence Scale (MMAS-8) questionnaire. The research sample was 261 pregnant women in eight villages in the Tongas Public Health Center (PHC) working area. A total of 50 Community Health Workers (CHWs) visited pregnant women’s homes weekly to give health education and monitoring activities from October 2022 to April 2023. The statistical test used Wilcoxon and Chi-square. Results: There is a significant difference in adherence between before and after the weekly home visit with a p-value < 0.001 and there is no correlation between adherence rate in the post-test and the level of education of mothers with a p-value > 0.05. The mothers know the benefit of supplementation and families support it. Conclusion: the CHW’s weekly home visit can effectively improve the iron supplementation intake among pregnant women regardless of the level of education, and improve the knowledge of supplementation benefits and family support. It is recommended to continue the activity and the budget, and include iron adherence materials in all health activities for pregnant women.